The role of cottage industry as a tool for rural and poor empowerment : the case of Kabong sub-district - Rosnah, Jali (Universiti Malaysia Sarawak, (UNIMAS), 2001)
The aim of this study is to identify or foresee the development of Cottage Industry in Kabong Sub-district as a tool for poverty alleviation and at the same time diversifies the community livelihood activities(to increase their income). Descriptive analysis (frequently distribution) was used to anlyze the quantitative components for this study. Correlation analysis and T-test also used to determine the relationship between the dependent variable and selected independents variables and differences between relevant groups respectively